Eksplorasi Potensi Bakteri Asosiasi Polymesoda erosa Sebagai Sumber Antibakteri dan Enzim untuk Bioindustri - Sayyidatur Rahma; Delianis Pringgenies; Wilis Ari Setyati (Universitas Diponegoro, 2026)
The bivalve Polymesoda erosa is known to harbor symbiotic bacteria that potentially produce secondary metabolites and extracellular enzymes with applications in health and bioindustry. This study aimed to: (1) characterize bacterial isolates associated with P. erosa from Semarang waters, and examine the enzymatic activity of potential isolates.. The research methods included bacterial isolation and purification using Nutrient Agar (NA), colony morphology characterization and Gram staining, antibacterial activity testing using the agar plug method against Escherichia coli and Staphylococcus aureus, and enzymatic assays (protease, amylase, lipase) on selective media. Selected isolates were further identified molecularly through 16S rRNA gene sequencing, BLAST analysis via NCBI, and phylogenetic tree construction. The results revealed five bacterial isolates with distinct morphological characteristics. Most isolates were Gram-positive with coccus, diplobacilli, and staphylococci forms. One isolate, B1.5.1 (a2), showed antibacterial activity against S. aureus. Enzymatic assays demonstrated that three isolates exhibited proteolytic, amylolytic, and lipolytic activities, with the highest activity recorded in isolate B1.5.1 (a2). Molecular identification confirmed that this isolate belonged to Enterobacter cloacae (100% homolog. In conclusion, the symbiotic bacteria of P. erosa exhibit diversity and possess significant potential as producers of antibacterial compounds and extracellular enzymes, highlighting their prospective role in sustainable bioindustry development.